The effects of different disinfectants and application conditions on microbial contaminants at dairy processing line - Pacheappan, Ganga Dewi; Samsudin, Nik Iskandar Putra; Hasan, Hanan (Wiley-Blackwell, 2021)
Disinfectants are very crucial in reducing microbial contaminants at dairy processing lines. However, there are limitations of their efficacy due to broad spectrum of microorganisms. Therefore, the aim of the present work was to investigate varying implementation conditions of disinfectants, Oxonia Active, Whisper V®, and carvacrol, that could give the highest reduction of foodborne pathogens. The killing efficacy of disinfectants were determined through suspension test at different concentrations (0.3‐1.0%), temperatures (25‐70°C), and contact times (5‐15 min) against six foodborne pathogens. 1.0% Oxonia Active at 25°C for > 10 min in suspension test achieved > 5 log CFU/mL microbial reduction for all foodborne pathogens with a complete elimination of Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. The application of Oxonia Active on the surface and biofilm tests (representing dairy processing equipment) showed significant microbial (pathogen) reduction (> 3 log CFU/mL) of 4 pathogens cocktail.